2017
DOI: 10.1002/jbio.201600255
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced phototoxicity of photodynamic treatment by Cx26‐composed GJIC via ROS‐, calcium‐ and lipid peroxide‐mediated pathways

Abstract: In spite of the promising initial treatment responses presented by photodynamic therapy (PDT), 5-year recurrence rates remain high level. Therefore, improvement in the efficacy of PDT is needed. There are reports showing that connexin(Cx) 26-composed gap junctional intercellular communication (GJIC) enhances the intercellular propagation of "death signal", thereby increasing chemotherapeutic cytotoxicity. However, it is unclear whether Cx26-formed GJIC has an effect on PDT phototoxicity. The results in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 33 publications
0
27
3
Order By: Relevance
“…Deng‐Pan Wu et al. from Xuzhou Medical University demonstrated the enhanced phototoxicity of photodynamic treatment by connexin 26‐composed gap junctional intercellular communication via ROS‐, calcium‐ and lipid peroxide‐mediated pathways . Weisong Shi et al.…”
Section: Research Interests Indicated By Jbpmentioning
confidence: 99%
“…Deng‐Pan Wu et al. from Xuzhou Medical University demonstrated the enhanced phototoxicity of photodynamic treatment by connexin 26‐composed gap junctional intercellular communication via ROS‐, calcium‐ and lipid peroxide‐mediated pathways . Weisong Shi et al.…”
Section: Research Interests Indicated By Jbpmentioning
confidence: 99%
“…Photofrin‐mediated PDT has firstly been approved in 1993 in Canada for the prophylactic treatment of bladder cancer . Our previous studies showed that homotypic Cx32‐ and Cx26‐composed GJIC‐mediated “bystander effect” could enhance the phototoxicity of Photofrin‐mediated PDT . The present study represented the first demonstration of the ability of heterotypic Cx32/Cx26‐composed GJIC to have a “Good Samaritan” effect on HeLa cells following Photofrin‐PDT treatment.…”
Section: Introductionmentioning
confidence: 50%
“…The Western blot assay was utilized as described in our previous studies . Briefly, after protein samples were separated, samples were transferred to nitrocellulose transfer membrane (Excell Bio, China).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations